Odpowiedzi

2009-10-22T21:24:01+02:00
Wiadomo, że \sqrt{a} : \sqrt{b} = \sqrt{a : b}

Zatem:

1) \sqrt{75} : \sqrt{3} = \sqrt{75 : 3} = \sqrt{25} = \sqrt{5 * 5} = 5

2) \sqrt{80} : \sqrt{5} = \sqrt{80 : 5} = \sqrt{16} = \sqrt{4 * 4} = 4

3) \sqrt{147} : \sqrt{3} = \sqrt{147 : 3} = \sqrt{49} = \sqrt{7 * 7} = 7

4) \sqrt{1440} : \sqrt{10} = \sqrt{1440 : 10} = \sqrt{144} = \sqrt{12 * 12} = 12

5) \sqrt{242} : \sqrt{2} = \sqrt{242 : 2} = \sqrt{121} = \sqrt{11 * 11} = 11

6) \sqrt{48} : \sqrt{3} = \sqrt{48 : 3} = \sqrt{16} = 4